2004
DOI: 10.1111/j.1365-2672.2004.02226.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Bacillus spp. belonging to the B. cereus and B. subtilis groups in Norwegian surface waters

Abstract: Aims: To investigate the presence and numbers of Bacillus spp. spores in surface waters and examine isolates belonging to the B. cereus and B. subtilis groups for cytotoxicity, and to discuss the presence of cytotoxic Bacillus spp. in surface water as hazard identification in a risk assessment approach in the food industry. Methods and Results: Samples from eight different rivers with variable degree of faecal pollution, and two drinking water sources, were heat shocked and examined for the presence of Bacillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…This showed that the organism can proliferate and produce toxin during the fermentation. The ability of B. cereus to contaminate food during processing has been reported (Ostensvik et al 2004). The results of our study established the possibility of this bacterium being a source of diarrhoea in Nigeria.…”
Section: Diarrhoeagenic Genessupporting
confidence: 74%
See 1 more Smart Citation
“…This showed that the organism can proliferate and produce toxin during the fermentation. The ability of B. cereus to contaminate food during processing has been reported (Ostensvik et al 2004). The results of our study established the possibility of this bacterium being a source of diarrhoea in Nigeria.…”
Section: Diarrhoeagenic Genessupporting
confidence: 74%
“…Among the strains of B. subtilis group studied in this work, diarrhoeagenic enterotoxin gene was only detected in B. licheniformis Lag1, although some of the isolates in this group were haemolytic on Colombia blood agar, the haemolysis on the blood agar does not confirm toxigenicity of the isolate similar observation has earlier been made (Ostensvik et al 2004). There is a dearth of information about the epidemiology of bacilli food borne diseases in Nigeria, but diseases from non-B.…”
Section: Diarrhoeagenic Genessupporting
confidence: 52%
“…As mentioned before, B. cereus produces multiple toxins, including hemolysins (HBL; 37.8, 38.5, and 43.5 kDa) (33) and NHE (39,45, and 105 kDa) (40). Based on the protein analysis data, PCR results, and hemolysis on blood agar plates, we speculate that cytotoxic action on Ped-2E9 cells could be due to the NHE and/or HBL components, since these toxins were also found to be involved in cytotoxic activities by using other cell lines (39). As indicated above, HBL possibly enhances Ped-2E9 cytotoxicity induced by NHE but is not essential.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the isolation of Gram's positive as well as Gram's negative bacteria from currency notes confirmed that currency might be playing an important role as a vector in the transmission of pathogenic bacteria in the community. For example some strains of Bacillus have been reported to be involved in food poisoning (Ostensvik et al, 2004). Similarly, Micrococcus sp.…”
Section: Results and Discussion:-mentioning
confidence: 99%